Answer:
30 plus 70 equals 100
Step-by-step explanation:
it tells the gum explicit equation
Answer:
the answer it $5.18
Step-by-step explanation:
$4.50 + ($4.50 x .15)
$4.50 + $0.68 = $5.18
Answer:
![f(n)=(-2)(n-1)](https://tex.z-dn.net/?f=f%28n%29%3D%28-2%29%28n-1%29)
Step-by-step explanation:
Each term of this Geometric Series (3, −6, 12, −24, ...) can also be found through this explicit formula:
Because the
term is found by the product of its common ratio "q", times its predecessor n-1. Where n, refers to the order of the term.
So let's test it, suppose we want to find the 4th term. We know the common ratio and the first term. Then we can write f(n) as:
![\\f(n)=3(-2)^{n-1}](https://tex.z-dn.net/?f=%5C%5Cf%28n%29%3D3%28-2%29%5E%7Bn-1%7D)
f(4)=f(3)*-2⇒-24=12*-2⇒-24=-24
The explicit formula is ok.
Answer:
6(3) - 4 + (3)^2
Explanation:
We will do this on two steps:
1- get g(x)-f(x)
2- substitute with x = 3
Step 1:
f(x) = 4-x^2
g(x) 6x
g(x) - f(x) = 6x - (4 - x^2)
= 6x - 4 + x^2
Step 2:
Substitute with x = 3 as follows:
g(x) - f(x) at x = 3 is:
6(3) - 4 + (3)^2
Hope this helps :)
Download photo math and it will let you take a picture of the equation and answer it for you